First Report of Leaf Rust on Blackberry ( Rubus spp.) Caused by Kuehneola uredinis in Florida - Marin, Marcus Vinicius; Seijo, Teresa E; Druffel, Keri; Deng, Zhanao; Peres, Natalia A (Plant disease, 2022)
During the fall of 2020 and summer of 2021, symptoms of leaf rust were observed on blackberry plants of 'Kiowa', and breeding line 1734 (progeny of 'Natchez' and Arapaho') in a field trial at the University of Florida, Wimauma, FL. Symptoms consisted of small chlorotic spots (1 to 3 mm) on the upper side of the leaf, while the underside had yellow-orange pustules. Disease incidence was up to 100% on both 'Kiowa' and the breeding line 1734, and severity was up to 20% with most of the symptoms observed on older leaves. Two isolates were collected from 'Kiowa' and one from the breeding line 1734 for further investigation. Isolates were maintained and multiplied on healthy 'Kiowa' plants in growth chambers (25 ºC and 12-12 h photoperiod). Uredinia (n=30) were erumpent and ranged from 90 to 320 µm (Average=285 µm, SD=5.3 µm) in diameter. Urediniospores (n=50) were obovoid, yellow, and ranged from 24 to 36 μm long (Average=32 µm, SD=3.2 µm) and 22 to 30 μm wide (Average=28 µm, SD=2.5 µm). Based on morphology and literature, the pathogen was tentatively identified as Kuehneola uredinis (Link) Arth (Arthur 1906; Shands et al., 2018). Spores from a single uredinium of each isolate were collected with a needle and suspended in 50 µL of molecular biology-grade water yielding a final concentration of approximately 5 x 104 spores/mL. Two µL of each spore suspension was used for the PCR reactions. Two DNA fragments were amplified using the primers Rust2inv and LR6, and Rust18S-R and NS1 for the 5.8S-ITS2-28S gene region of rDNA (1,755 bp) and partial 18S gene region of rDNA (2,684 bp), respectively. The amplified products of the partial 28S gene region were sequenced with the primers LR3 and LR0R, and the 18S gene region with NS5, NS6, and NS4 (Aime 2006). DNA sequences were deposited in GenBank (accession nos. OK509845 - OK509848). BLASTn searches revealed that the isolates were 100% identical to reported causing leaf rust on blackberry in California (1044/1044bp, and 1540/1540bp for accession numbers MF158087, and MF158088, respectively). To test for pathogenicity, blackberry cultivars Kiowa, Natchez, Osage, Ouachita, Ponca, Prime-Ark® 45, Prime-Ark® Freedom, Prime-Ark® Traveler, and Prime-Ark® Horizon were inoculated. Five plants of each cultivar were inoculated with a mixture of spores of the three isolates, and two plants of each cultivar were used as controls. Spores were washed from leaves of 'Kiowa' exhibiting sporulation using a suspension of 1% Tween 20 in deionized water. The final concentration of the inoculum was adjusted to 104 spores/mL. Plants were inoculated in the greenhouse with a spray bottle until run-off and kept inside clear plastic boxes for 48 h. Controls were sprayed with sterile deionized water. Plants were watered by mists of 3 s every 10 min twice a week. Disease incidence and severity were evaluated weekly on five leaves per plant that had been tagged before inoculation. The experiment was repeated once. Symptoms identical to the original were only observed in 'Kiowa' and 'Prime-Ark® Freedom'. One week after inoculation, disease incidence was already 100% in both cultivars, with at least one pustule on all the inoculated leaves, and six weeks later disease severity was up to 50% (Average= 35%, SD=2.4%). To our knowledge, this is the first report of causing leaf rust on blackberry in Florida. This disease was reported on spp. in several U.S. states, and recently in California on (Farr and Rossman 2021; Shands et al. 2018). Blackberry is an emerging crop in Florida and efforts should be implemented to monitor the occurrence and spread of leaf rust considering that urediniospores disperse long distances by wind, especially if growers choose the susceptible cultivars 'Kiowa' and 'Prime-Ark Freedom'. The apparent resistance observed in other commercial cultivars such as 'Osage', 'Ouachita', and 'Ponca' may serve as valuable breeding parents for developing new blackberry cultivars with resistance to leaf rust.